2004
DOI: 10.1111/j.1477-8947.2004.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Water, women and community in Trinidad, West Indies

Abstract: This article examines the history and character of the water supply in Trinidad and Tobago and the nature of problems associated with the procurement of water by Trinidadians. The article reports on case studies of two rural communities in which women have taken the lead to solve water problems. It reflects on the importance of small‐scale, community‐managed water systems for the possibility of achieving water democracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The earlier gains made in providing water services are being undermined by aging infrastructure and the difficulties of keeping pace with rising demands placed on the systems, especially by urban and tourism-related developments. The extent and impact of disparities in distribution and access to water services has been, with a few exceptions, underresearched (see Mycoo, 2007;Schneiderman & Reddock, 2004). Some Caribbean states have over the last decade made efforts to adapt the institutional arrangements in their water sectors but as might be expected, and given the disparities between states in the region, these vary.…”
Section: Water Resources and Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earlier gains made in providing water services are being undermined by aging infrastructure and the difficulties of keeping pace with rising demands placed on the systems, especially by urban and tourism-related developments. The extent and impact of disparities in distribution and access to water services has been, with a few exceptions, underresearched (see Mycoo, 2007;Schneiderman & Reddock, 2004). Some Caribbean states have over the last decade made efforts to adapt the institutional arrangements in their water sectors but as might be expected, and given the disparities between states in the region, these vary.…”
Section: Water Resources and Consumptionmentioning
confidence: 99%
“…At the same time, water service providers can have rates of unaccounted or nonrevenue water up to 60%, depending on whose figures are accepted, which in itself is an indication of the serious lack management information. Unmet demand for water is not uncommon; for example, it has been reported that only 14% of Trinidadians received an uninterrupted water supply and that the difference between estimated demand and actual supply in 2000 was 11% (Schneiderman & Reddock, 2004). Recently, Trinidad's Water and Sewerage Authority announced that it wants to invest in increased storage and construct a new national water transmission network in order to achieve "water for all" (Guardian, April 14, 2008).…”
Section: Water Resources and Consumptionmentioning
confidence: 99%
“…Limited access to potable water in informal settlements calls for refocusing engineering education to find effective solutions to improve water access. Firstly, women in informal settlements spend much time collecting water for domestic use [18] [19]. Secondly, the state provides subsidised standpipe water or truck borne water because conventional piped water supply is costly to provide in informal settlements located on hilly terrain and service interruptions are common.…”
Section: Engineering Education and Water Provision In Informal Settlementioning
confidence: 99%
“…These communities are, in many cases, creating their own water delivery systems, as they would not have been reached and served by the AAA. In other cases, these systems supplement existing deficient water delivery services, or as in Trinidad, serve communities who used to have water delivery but then were abandoned and ignored after system failures (Scheniederman and Reddock 2004). Usually, these systems are the only reliable source of water for communities that may not be served at all due to the topography of their location, or the infrastructure only serves water in an interrupted and intermittent unreliable, almost nonexistent schedule (Minnigh and Ramírez Toro 2001).…”
Section: Honing the Local Freshwater Supply: Local And Regional Watermentioning
confidence: 99%